2021
DOI: 10.1126/sciadv.abe0985
|View full text |Cite
|
Sign up to set email alerts
|

Inside the STEM pipeline: Changes in students’ biomedical career plans across the college years

Abstract: Researchers often invoke the metaphor of a pipeline when studying participation in careers in science, technology, engineering, and mathematics (STEM), focusing on the important issue of students who “leak” from the pipeline, but largely ignoring students who persist in STEM. Using interview, survey, and institutional data over 6 years, we examined the experiences of 921 students who persisted in biomedical fields through college graduation and planned to pursue biomedical careers. Despite remaining in the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Researchers also find support for the predictions using other kinds of methods. For instance, Rosenzweig et al (2021) interviewed a large sample of college students who either stayed in STEM majors or opted out. They found that the students’ task values were the key predictor of their choice.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also find support for the predictions using other kinds of methods. For instance, Rosenzweig et al (2021) interviewed a large sample of college students who either stayed in STEM majors or opted out. They found that the students’ task values were the key predictor of their choice.…”
Section: Discussionmentioning
confidence: 99%
“…That more older, returning students, women, and members of underrepresented racial minority groups report such positive value perceptions and trajectories suggests that at this particular institution, the oft referenced “STEM pipeline” may indeed be broadening (Maltese & Tai, 2011; Sass, 2015). As scholarship focused on the experiences of STEM learners moves away from the STEM pipeline metaphor and reorients away from deficit oriented “leaks” of students from it (Cannady et al, 2014), the accounts of students as they persist through STEM learning experiences become central to the narrative about STEM training opportunities (Rosenzweig et al, 2021). Our quantitative findings make an empirical case for additional exploration that can more precisely capture the observed motivational trajectories of specific cultural groups within the underrepresented minority group (Cokley & Awad, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…To measure long-term persistence, we examined students’ academic majors 2.5 y postintervention, which was the end of junior year for most students in the sample. This is a critical juncture in a student’s academic trajectory: By this timepoint, all students are required to declare a major and their academic plans have stabilized ( 26 ). In our sample, 73% of students were majoring in a STEM field at this timepoint.…”
Section: Methodsmentioning
confidence: 99%